Adipokines: Metabolic link between knee osteoarthritis and obesity - Poonpet, PhD, Thitiya; Honsawek, MD, Sittisak (Journal of Southeast Asian Orthopaedics, 2022)
Osteoarthritis (OA) is a heterogeneous and multifactorial process of chronic degenerative joint disorder that involves not only articular cartilage, but also synovium, subchondral bone, and surrounding muscles and ligaments. Obesity is a well known risk factor of the incidence and prevalence of osteoarthritis and is believed to play a deleterious part in knee OA by the increment in mechanical stresses on the joints. The role of obesity in knee OA is much more complicated than previously thought. Adipokines, cytokines mainly produced by adipose tissue, may play a potential role in knee OA. In this review, we summarize the recent advances in adipokine research in knee osteoarthritis, focusing on leptin, adiponectin, visfatin, and resistin, and also the essential role of newly identified adipokines such as chemerin, lipocalin, and omentin.